Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD

Direct synthesis of nanocrystalline silver from the reaction between silver carboxylates and n-trioctylphosphine - Charan, Shobhit; Singh, Narendra; Khanna, P. K.; Patil, K. R. (Journal of Nanoscience and Nanotechnology, 2006)
Neat n-Trioctylphosphine (TOP) has been used for the first ever time for reduction of silver nitrate and silver carboxylates (citrate, oleate, and myristate) under mild thermal reaction conditions. UV-visible absorption measurements of re-dispersible silver particles that were obtained by reduction of silver myristrate (product-IV) and silver nitrate (product-I) showed surface plasmon resonance absorption peak at 400 nm. The powder XRD pattern of fcc zero-valent silver resulted in diameters in the range of about 25-30 nm. TEM analysis showed particle diameter similar to that was observed by the XRD. FTIR spectroscopy revealed that the organics from the carboxylate group are retained by the nano-particles in case of product-IV however, presence of TOP is observed in product-I. It is found that when silver nitrate is reduced by TOP, spherical silver nano-particles with poor redispersity are formed but extended heating results in formation of long silver rods of micrometer size however, the re-dispersible nano-particles are easily formed when silver carboxylates are reduced by TOP.
Keywords: Chemical synthesis; Nanocrystalline; noble metal; XRD

Unusual formation of nano-particles of CdO and Cd(OH)(2) from the reaction of dimethyl cadmium with DMF - Singh, Narendra; Charan, Shobhit; Patil, K. R.; Viswanath, A. K.; Khanna, P. K. (Materials Letters, 2006)
This paper presents generation of CdO and Cd(OH)(2) nano-particles from Dimethyl Cadmium in DMF. The CdO nano-particles were obtained instead of CdSe, even when the reaction was done in presence of 1,2,3-selenadiazole (the source of selenium) with Me2Cd in DMF (product-I). The direct reaction of Me2Cd in DMF also leads to formation of CdO (product-II). However, Cd(OH)(2) nano-particles were obtained when Me2Cd was refluxed in DMF for a few hours followed by reaction of H2S gas (product-III). The formation of Cd(OH)(2) was also established via decomposition Of Me2Cd:Et2O adduct (product-IV). Nano-particles of CdO and Cd(OH)(2) (product-I to product-IV) were characterized by X-ray powder diffraction (XRD), TEM and SEM/EDS measurements, FTIR, thermal analysis (TGA) and XPS analysis. The particle size of all the products as calculated by XRD patterns were in the range of about 20 nm. TEM images showed that the products are agglomerated clusters with the particles in the nano-meter regime. The synthesis however, is understood to be unusual as the reactions with selenium source and sulfur source should have generated the CdSe and CdS however, the end products were always found to be the product-I to product-IV (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Nanoparticles; Semiconductor; XRD